First evidence on the causal association between green tea and gastrointestinal health: a two sample mendelian randomization study - Zhixiong Jiang; Renlan Li; Yi Li (CyTA - Journal of Food)
In light of the persisting ambiguity surrounding the causality between green tea intake and gastrointestinal health, this study endeavors to elucidate it using mendelian randomization. Leveraging data from the UK Biobank and FinnGen database, instrumental variants were selected from single-nucleotide-polymorphisms associated with green tea intake. The inverse-variance-weighted method served as the primary analytical approach. Rigorous scrutiny of the results encompassed the Egger intercept test, Mendelian Randomization Presso, Cochran Q test, leave-one-out test, and funnel plot. The primary findings underscore a significant association between green tea intake and gastrointestinal diseases (p = 0.001), indicating heightened consumption of green tea could lead to a reduced risk of gastrointestinal diseases (odds ratio = 0.994). Robustness assessments across all measures substantiate the credibility of these outcomes (all p > 0.05). In conclusion, this study supports the assertion that green tea confers beneficial effects on gastrointestinal health.